Researcher Profile: An Interview With Dr. Rebecca J. Travnichek - Rebecca J Travnichek (Journal of Financial Therapy, 2011)
Dr. Rebecca Travnichek is a Family Financial Education Specialist with University of Missouri Extension. Dr. Travnichek currently serves as the Annual Conference Program Chair. She is also very active in the Association for Financial Counseling and Planning Education, where she serves on the Board of Directors. Dr. Travnichek has participated in leadership development programs at the state and national levels. She was involved in the initial proposal development of the Financial Security for All Community of Practice with eXtension and continues to be involved through several roles. She is active in the National Extension Association of Family and Consumer Sciences at the national and state levels, serving in multiple leadership roles. For the past three years, Dr. Travnichek has also served as the Editor of the Journal of the National Extension Association of Family and Consumer Sciences. She represents the type of person who makes the Financial Therapy Association a dynamic organization linking practitioners and academicians.
Keywords: Financial Education and Planning